Ferramenta para avaliação da presença de práticas de simbiose industrial em uma rede de empresas - Saraceni, Adriana Valélia (2014)
The main objective of this research was to develop a tool for assessing the presence of Industrial Symbiosis practices in na industrial cluster, based on the concepts of Industrial Symbiosis found in the literature. For this, were conceived a variety of steps to form theoretical framework of this research, and, for the development of the proposed methodology. In order to form the bibliographic portfolio, this research initial steps were based on the instrument ProKnow-C (Knowledge Development Process–Constructivist). This procedure was performed with support of ISI Web of Knowledge portal and carried out in two categories of classification: Engineering, Environmental and Engineering, Industrial. Based on this differentiated systematic review, the variables of Industrial Symbiosis were identified. The results obtained by this procedure allowed the development of the theoretical model. After identificatifying the variables, a methodology based on fuzzy logic was applied and directed to the researchers of the subject for assigning weights of the variables of Industrial Symbiosis. Thus, it was possible to extract indicators of intensity of the interrelationships, these, needed in the analysis of the level of development of each of the correlations between the variables. In possession of the variables and their indicators, it was obtained an structure of the theoretical model for Assessing of Industrial Symbiosis, as initial result. In order to promptly identify gaps or development levels within each sphere, graphs of maneuver for data analysis were generated. After these procedures, it was built a tool to the model application, accompanied by a mathematical calculation method for processing data, making it reliable for implementation, compilation and results. Therefore, a model able to implementing the methodology, able to obtain the data for analysis on the graphs of maneuver and to generate the Assessing Industrial Symbiosis, was developed. Finally, a pilot test was conducted in a Industrial Cluster of manufacturer of furniture and wooden frames, identifying whether there are Industrial Symbiosis practices in the cluster, as well as the potential of development in the spheres of analysis. The results of the pilot test of the model for Assessing Industrial Symbiosis provided a range of perspectives related to its applicability, flexibility, features and guidance on aspects of ripening the tool.